HAMBATAN DAN TANTANGAN PENERAPAN KURIKULUM MERDEKA DI KELAS IV SDN 6 MEKARJAYA - Gani, Abdul; Jenal Mutaqin, Ejen; Nadiroti Muslihah, Neni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the obstacles and challenges in implementing the Merdeka Curriculum in grade IV of SDN 6 Mekarjaya. The Merdeka Curriculum emphasizes student‑centered learning, project‑based learning, and the development of the Pancasila Student Profile. However, its implementation faces several barriers, including limited teacher understanding, inadequate learning facilities, and diverse student characteristics. This research employed a qualitative descriptive method with observation, interviews, and documentation as data collection techniques. The findings reveal that teachers encounter difficulties in designing learning modules, conducting diagnostic assessments, and applying project‑based learning due to limited resources. Moreover, students’ varied abilities and parental involvement also influence the effectiveness of curriculum implementation. The study concludes that collaborative efforts between teachers, schools, and parents are essential to overcome these challenges. Recommendations include continuous teacher training, provision of adequate learning facilities, and strengthening school–parent partnerships to ensure successful implementation of the Merdeka Curriculum.